Two for the Money - Caruso, D. J.; Al Pacino, 1940-; Matthew McConaughey; Rene Russo; Armand Assante; Jeremy Piven; Jaime King; Kevin Chapman; Ralph Garman; Gedde Watanabe; Carly Pope; Charles Carroll; et al. (USA Universal Pictures, 2005)
After suffering a career-ending injury, a former college football star aligns himself with one of the most renowned touts in the sports-gambling business.
Brandon Lang loves football: an injury keeps him from the pros, but his quarterback's anticipation makes him a brilliant predictor of games' outcomes. Needing money, he leaves Vegas for Manhattan to work for Walter Abrams advising gamblers. Walter has a doting wife, a young daughter, and a thriving business, but he has problems: a bum heart, a belief he's a master manipulator, and addictions barely kept in check. He remakes Brandon, and a father-son relationship grows. Then, things go awry. Walter may be running a con. The odds against Brandon mount.
Languages : English, Turkish Subtitles : English, Turkish
Keywords: Drama; Sport; Thriller